2022
DOI: 10.1093/plcell/koac243
|View full text |Cite|
|
Sign up to set email alerts
|

BREEDIT: a multiplex genome editing strategy to improve complex quantitative traits in maize

Abstract: Ensuring food security for an ever-growing global population while adapting to climate change is the main challenge for agriculture in the 21st century. Although new technologies are being applied to tackle this problem, we are approaching a plateau in crop improvement using conventional breeding. Recent advances in CRISPR/Cas9-mediated gene engineering have paved the way to accelerate plant breeding to meet this increasing demand. However, many traits are governed by multiple small-effect genes operating in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 92 publications
0
37
0
Order By: Relevance
“…In the past few years, studies have demonstrated the feasibility of CRISPR-based knockout collections in rice (Oryza sativa L.), maize (Zea mays) and tomato (Solanum lycopersicum) 12,[15][16][17][18][19][20][21][22] . However, thus far, CRISPR/Cas9 has not been used on a genome-scale level to simultaneously target multiple potentially redundant genes in plants or other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, studies have demonstrated the feasibility of CRISPR-based knockout collections in rice (Oryza sativa L.), maize (Zea mays) and tomato (Solanum lycopersicum) 12,[15][16][17][18][19][20][21][22] . However, thus far, CRISPR/Cas9 has not been used on a genome-scale level to simultaneously target multiple potentially redundant genes in plants or other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…MGE in maize can also be performed with a larger number of sgRNAs. For instance, vectors harboring up to twelve individual sgRNA expression cassettes have been successfully used for the transformation of an “editor” (i.e., Cas9-expressing) maize line ( Lorenzo et al, 2022 ). Gong et al (2021 ) compared the CRISPR/Cas12a versus the CRISPR/Cas9 system for MGE targeting the maize bZIP transcription factor Opaque2 ( O2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In BREEDIT, populations transformed with different sets of sgRNAs (twelve different sgRNAs on each set) are then crossed, stacking up mutations in an increasing number of genes. This approach is useful for both trait improvement as well as for the discovery of new genes contributing to a given trait of interest ( Lorenzo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Six primary research articles in this issue address topics related to abiotic stress and climate change. Lorenzo et al (2023) present a gene discovery pipeline in maize called BREEDIT, combining multiplex genome editing of whole gene families with crossing schemes to improve complex traits such as yield and drought tolerance. Two articles report on proteins that function in guard cells, one related to abscisic acid (ABA)-activated Ca 2+ signaling ( Tan et al, 2023 ) and the second describing a module that regulates microtubule disassembly ( Wang et al, 2023 ).…”
mentioning
confidence: 99%